Population dynamics of Commelina benghalensis L. under soil and herbicide management practices - Voll, Elemar (1997)
One experiment was carried out on field, on a Dusky-Red dystrophic Latosol, in Londrina, PR, Brazil, during 1989-94. The objectives were to determine: a) the reduction rate of Commelina benghalensis L. seedbank; b) the Commelina seed distribution throughout the soil profile, and its evolution; c) the Commelina survival; and d) the rate of emergence of a Commelina seedbank in pre and postsowing of soybean. Four soil managements, and two with herbicide, in soybeans, after wheat, were studied. A complete randomized experiment, with split-plots, and four replications was used. Annual reducing rates of the seedbank in the soil managements as moldboard (9.9%), conventional (10.3%), scarification and heavy disc (13.8%), and no-till (18.7%) were observed with the use of postemergence herbicides; with no control, by competing with Brachiaria plantaginea (Link) Hitch., the rates were of 23.1%, 19.3%, 23.0% and 28.6%, respectively, possibly showing allelopathic effects. Estimated survival periods varied between 22.5 and 42.6 years, with herbicide control; by competing with B. plantaginea, they varied between 13.6 and 21.3 years. Emergence rates were not significant at soybeans pre-sowing. Postemergence rates varied only by year, between 0.8% and 3.7%, showing late emergence in the season. After corrective liming, which was conducted before wheat sowings, higher emergence rates for the specie occurred.